Hypertension induced by chemotherapeutic and immunosuppresive agents: A new challenge. Issue 1 (January 2015) - Abi Aad, Simon; Pierce, Matthew; Barmaimon, Guido; Farhat, Fadi S.; Benjo, Alexandre; Mouhayar, Elie
Highlights Hypertension is a common adverse effect of certain anti neoplastic therapy. We reviewed the literature for studies that reported the effect of anti neoplastic agents on blood pressure in patients with malignancies. 30% of patients treated for cancer will have concomitant hypertension, and crucial chemotherapy can sometimes be stopped due to new onset or worsening severe hypertension. Hypertension in this group of patients, if untreated, can alter cancer management and result in dose reductions or termination of treatments as well as life-threatening end organ damage.